Community health worker insights on promoting research engagement with diverse populations - Killough, Cynthia M.; Madaras, Annemarie; Phillips, Christina; Hettema, Jennifer; Ceballos, Venice; Fuentes, Jesus E.; Rishel Brakey, Heidi; Wagner, Katherine; Page, Kimberly (Frontiers in Public Health, 2023)
Representation of diverse populations in health research enhances our ability to understand the factors that impact health, generalize results, implement findings, and promote social justice. The primary objective of the study was to understand the unique perspectives of frontline community health workers (CHWs) to identify actionable barriers and facilitators that may impact representation of diverse groups in health research. Focus groups with CHWs were conducted followed by thematic analysis. Results revealed five main themes: barriers/risks to research participation, facilitation of research, CHW roles, recommendations, and transparency. A novel finding was that some CHWs see themselves as both facilitators and gatekeepers. As facilitators, CHWs ensure their patient populations receive resources and benefit from being involved in research; as gatekeepers CHWs feel that they protect patient populations from experiencing further trauma, especially when engaging in research. Recognizing that in many communities there is a high reliance and trust with CHWs, can promote genuine and informed participation at all stages of research.